MagicPlate‐512: A 2D silicon detector array for quality assurance of stereotactic motion adaptive radiotherapy. Issue 6 (21st May 2015) - Petasecca, M.; Newall, M. K.; Booth, J. T.; Duncan, M.; Aldosari, A. H.; Fuduli, I.; Espinoza, A. A.; Porumb, C. S.; Guatelli, S.; Metcalfe, P.; Colvill, E.; Cammarano, D.; et al.
Abstract : Purpose: Spatial and temporal resolutions are two of the most important features for quality assurance instrumentation of motion adaptive radiotherapy modalities. The goal of this work is to characterize the performance of the 2D high spatial resolution monolithic silicon diode array named "MagicPlate‐512" for quality assurance of stereotactic body radiation therapy (SBRT) and stereotactic radiosurgery (SRS) combined with a dynamic multileaf collimator (MLC) tracking technique for motion compensation. Methods: MagicPlate‐512 is used in combination with the movable platform HexaMotion and a research version of radiofrequency tracking system Calypso driving MLC tracking software. The authors reconstruct 2D dose distributions of small field square beams in three modalities: in static conditions, mimicking the temporal movement pattern of a lung tumor and tracking the moving target while the MLC compensates almost instantaneously for the tumor displacement. Use of Calypso in combination with MagicPlate‐512 requires a proper radiofrequency interference shielding. Impact of the shielding on dosimetry has been simulated bygeant4 and verified experimentally. Temporal and spatial resolutions of the dosimetry system allow also for accurate verification of segments of complex stereotactic radiotherapy plans with identification of the instant and location where a certain dose is delivered. This feature allows for retrospective temporal reconstruction of the delivery process and easy identification of error in the tracking or the multileaf collimator driving systems. A sliding MLC wedge combined with the lung motion pattern has been measured. The ability of the MagicPlate‐512 (MP512) in 2D dose mapping in all three modes of operation was benchmarked by EBT3 film. Results: Full width at half maximum and penumbra of the moving and stationary dose profiles measured by EBT3 film and MagicPlate‐512 confirm that motion has a significant impact on the dose distribution. Motion, no motion, and motion with MLC tracking profiles agreed within 1 and 0.4 mm, respectively, for all field sizes tested. Use of electromagnetic tracking system generates a fluctuation of the detector baseline up to 10% of the full scale signal requiring a proper shielding strategy. MagicPlate‐512 is also able to reconstruct the dose variation pulse‐by‐pulse in each pixel of the detector. An analysis of the dose transients with motion and motion with tracking shows that the tracking feedback algorithm used for this experiment can compensate effectively only the effect of the slower transient components. The fast changing components of the organ motion can contribute only to discrepancy of the order of 15% in penumbral region while the slower components can change the dose profile up to 75% of the expected dose. Conclusions: MagicPlate‐512 is shown to be, potentially, a valid alternative to film or 2D ionizing chambers for quality assurance dosimetry in SRS or SBRT. Its high spatial and temporal resolutions allow for accurate reconstruction of the profile in any conditions with motion and with tracking of the motion. It shows excellent performance to reconstruct the dose deposition in real time or retrospectively as a function of time for detailed analysis of the effect of motion in a specific pixel or area of interest.